2023
DOI: 10.1111/ceo.14237
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of ocular disease in children aged between 0 and 3 years at an Australian paediatric tertiary hospital

Abstract: BackgroundChildhood ocular disease can be a significant health burden to the child, family and society. Previous studies have examined the spectrum of paediatric ocular disease presenting to tertiary hospitals; however, these studies have broader age ranges, smaller sample sizes, and are largely based in developing countries. This study aims to assess the spectrum of ocular disease in the first 3 years of life presenting to the eye department of an Australian tertiary paediatric hospital.MethodsThe records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Further, the common cause for unilateral anomalies is micro-phthalmous followed by congenital ptosis. LO-COA et al [ 8 ] shows unilateral visual impairment micro-phthalmos (5.5%). This is similar to our data with unilateral involvement (2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the common cause for unilateral anomalies is micro-phthalmous followed by congenital ptosis. LO-COA et al [ 8 ] shows unilateral visual impairment micro-phthalmos (5.5%). This is similar to our data with unilateral involvement (2%).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies report the prevalence of congenital NLDO varies from 5 % to 20 % in early childhood. Bilateral is more common in NLD obstruction [ 8 ]. Tupe et al [ 10 ] observed that in 18 cases (36%) parents gave a history of consanguinity, of these 16% had 1st degree of consanguinity, 78% had 2nd degree consanguinity and only 6% subject's 3rd degree consanguineous relations in marriage.…”
Section: Discussionmentioning
confidence: 99%